Does ESG always improve corporate performance? Evidence from firm life cycle perspective - Gao, Shang; Meng, Fanchen; Wang, Wenshuai; Chen, Wenxin (Frontiers in Environmental Science, 2023)
In this study, drawing on firm life cycle theory, we focus on the corporate performance of ESG engagement via financial stress and consider the moderate effect of transparency, financial slack, and environmental uncertainty. The industry-year fixed effects panel regression analysis is executed based on the data, including 11,742 firm-year observations for 1486 Chinese A-share listed companies from 2010 to 2020. The results show that ESG performance can significantly improve corporate performance at all life cycle stages, especially when the corporate is in the growth stage. Moreover, the mechanism analysis shows that the financial risk mediates the relation between ESGP and corporate performance for the corporates in the growth and maturity stages. The association between ESG and corporate performance is more pronounced when corporate information disclosure quality is high. Moreover, financial slack moderates and undermine the association between ESG and corporate performance in the maturity stages. Similarly, for the maturity and decline stages of corporate, environmental uncertainty moderates and undermines the association between ESG and corporate performance.